Effect of layer thickness on the mechanical properties of laser sintered PA12 - Lee, Shin Da (2016)
Being the trendiest Additive Manufacturing method in industry application as its wide material range availability and complex shape printing ability, Selective Laser Sintering still has extensive range of unidentified properties in the material and process factor employed. The author has conducted several mechanical testings include tensile testing, impact testing and hardness testing to determine the effect of layer thickness on Polyamide 12 (PA12). Additionally, degree of crystallization of material in various section thicknesses with two categories of layer thickness (100 and 120µm) were obtained by differential scanning calorimetry and to explain the outcome of mechanical testings. The polished surfaces of PA12 with different layer thicknesses were also observed by the author under optical microscope.